2005
DOI: 10.1007/s10397-004-0076-2
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of abnormal uterine bleeding in perimenopausal women by hysteroscopy and endometrial biopsy

Abstract: The causes of abnormal uterine bleeding (AUB) during the perimenopausal period in women receiving hormone replacement therapy (HRT) were investigated, along with the causes of postmenopausal bleeding, the efficacy of hysteroscopy in the diagnosis of endometrial pathology was investigated. The patients studied were referred to our academic gynaecological clinic during the period 1999-2003. 145 cases that had undergone hysteroscopy and endometrial biopsy for AUB during the perimenopausal period over the last fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Fourteen authors were contacted and asked for additional data, 3 responded whereas 11 did not respond and had to be excluded. In total, 54 studies were excluded because of various reasons as shown in Figure 1 2,16–68 . Finally 17 studies with 4208 procedures remained, and were included in our meta‐analysis 69–85 .…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen authors were contacted and asked for additional data, 3 responded whereas 11 did not respond and had to be excluded. In total, 54 studies were excluded because of various reasons as shown in Figure 1 2,16–68 . Finally 17 studies with 4208 procedures remained, and were included in our meta‐analysis 69–85 .…”
Section: Resultsmentioning
confidence: 99%
“…Hysteroscopy of reproductive tracts became commonly used in humane medicine as a method of diagnosing infertility, polyps, hyperplasia, neoplasm, endometriosis (Stamatellos et al, 2005;Makled et al, 2014). Also, this method of diagnostics is recommended as the prior investigation in cases of cow infertility (Šavc et al, 2011).…”
mentioning
confidence: 99%